2021
DOI: 10.1177/21582440211002215
|View full text |Cite
|
Sign up to set email alerts
|

Urban and Rural Income Gap: Does Urban Spatial Form Matter in China?

Abstract: This research uses satellite remote sensing data to measure the urban spatial form and analyzes the impact of changes to urban spatial structure on the income gap between urban and rural residents. The results indicate that the compactness of the urban spatial form is positively correlated with the income gap between urban and rural residents. However, there is no statistically significant relationship between the urban spatial extension rate and the urban–rural income gap. A subsequent analysis of the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Moreover, the urban-oriented financial expenditure structure prevalent in developing countries gives urban residents substantial advantages over rural residents in terms of access to housing, education, medical care, and other social benefits. The findings of some scholars also proved this result (Liu & Long, 2021;Zhong et al, 2022). The increase in the proportion of second industry is conducive to narrowing the urban-rural income gap, which also confirms the shrinking effect of the expansion scale.…”
Section: Impact Analysis Of the Control Variablesmentioning
confidence: 63%
“…Moreover, the urban-oriented financial expenditure structure prevalent in developing countries gives urban residents substantial advantages over rural residents in terms of access to housing, education, medical care, and other social benefits. The findings of some scholars also proved this result (Liu & Long, 2021;Zhong et al, 2022). The increase in the proportion of second industry is conducive to narrowing the urban-rural income gap, which also confirms the shrinking effect of the expansion scale.…”
Section: Impact Analysis Of the Control Variablesmentioning
confidence: 63%
“…4 However, to our knowledge, no study has looked at the relationship between urbanization and income inequality using these new income inequality indicators. Consistent with these arguments, it compels us to consider a further investigation, which has been highly recommended by previous studies (Liu & Long, 2021;Sulemana et al, 2019).…”
Section: Introductionmentioning
confidence: 65%
“…Utilizing four dimensions-urban-rural spatial integration, economic integration, social integration, and ecological integration-a set of 22 indicators was established, covering 16 aspects including spatial aggregation level, spatial connectivity efficiency, digitalization level, population density, economic conditions, industrial structure, employment situation, resident income, consumer spending, technological progress, education inclusivity, material foundation, pursuit of cultural life, healthcare, vegetation greening, and energy consumption. The objective was to construct a multidimensional evaluation index system that comprehensively reflects the actual level of urban-rural integration in China [52][53][54]. Through the comprehensive assessment of these indicators, it becomes possible to accurately reflect the differences and development situations of the urban-rural integration level across different provinces in China.…”
Section: Variable Selectionmentioning
confidence: 99%
“…Typically, government interventions propel economic growth via specific institutional frameworks. Liu et al [54] observed a pervasive trend across developing countries where fiscal allocations are disproportionately skewed towards urban areas, thereby endowing urban dwellers with a social welfare advantage over their rural counterparts, and fostering a disparity in development between urban and rural regions. Such fiscal practices could hinder the equitable distribution of resources based on market demands, leading to discrepancies in resource allocation across sectors.…”
Section: Variable Selectionmentioning
confidence: 99%